ABCB6 knockdown suppresses melanogenesis through the GSK3-β/β-catenin signaling axis in human melanoma and melanocyte cell lines. Issue 2 (May 2022) - She, Qiuyun; Dong, Yingying; Li, Dong; An, Ran; Zhou, Ting; Nie, Xiaoqi; Pan, Ronghua; Deng, Yunhua
Abstract: Background: Melanogenesis is a multistep process in which melanocytes produce melanin pigments within melanosomes. However, the roles played by the biological factors and pathways in this process are not yet fully understood. Objective: To investigate the role of ATP-binding cassette subfamily B member 6 (ABCB6) in the regulation of melanogenesis in vitro. Methods: Real-time PCR and western blotting were used to assess the knockdown efficiency of ABCB6 in MNT-1 and PIG1 stable cell lines. Cleavage by NaOH was used to determine melanin content, while the number of melanosomes was examined for each stage by transmission electron microscopy. Immunofluorescence microscopy was used to evaluate endogenous protein location. Differentially expressed genes were detected using RNA sequencing, and gene expression was assessed by quantitative real-time PCR. KEGG mapping was used for pathway enrichment analysis. Co-immunoprecipitation was used for protein-protein interactions analysis. Results: We found that ABCB6 inhibition could impair melanocyte maturation and melanin production in human melanoma (MNT-1) and immortalized human melanocyte (PIG1) cell lines. Moreover, ABCB6 knockdown inhibited the protein expression of melanocyte inducing microphthalmia-associated transcription factor (MITF) and its three downstream melanogenic enzymes (TYR, TYRP1 and TYRP2). Mechanistically, we revealed that ABCB6 could interact with and modulate glycogen synthase kinase 3 beta (GSK3-β) to exert its biological effect on melanogenesis. Conclusion: Our findings suggest that ABCB6 is a key regulator of melanogenesis via the GSK3-β/β-catenin signaling pathway. However, further in-depth studies are essential to uncover the relationship between ABCB6 and pigmentation disorders. Highlights: ABCB6 is a key protein in the maturation process of melanosomes in MNT-1 and PIG1 cells. ABCB6 regulates melanin synthesis and the expression of melanin-related proteins. ABCB6 modulates melanogenesis through the GSK3-β/β-catenin signaling axis.